Occurrence of Diabetes among Rural Women - Randhawa, Jasjit Kaur; Singh, Zorawar; Sonia (Journal of Diseases, 2020)
Diabetes has already been described as an epidemic, and health care system around the world is bearing its pressure. Globally, it has to be dealt with huge care. In the present study, 1001 rural women (Age 21-90 years; mean age: 54 ± 3.2 years) from the northern region of Punjab were analyzed for the serum glucose levels, to estimations its occurrence/prevalence. The subjects were divided into different age groups. The study revealed a high percentage (46.2%) of subjects with serum glucose levels higher than the normal range of 70-110 mg/dl of blood. Age groups of 21-30 and 81-90 years showed a less prevalence of diabetes, whereas age groups between 31-40 and 41-50 years is most prone showing higher percentages (average 12.9 and 18.5%, respectively). The study is an indicative of a major crisis in the coming times. The data suggests that awareness drives and remedial measures should be enforced with immediate effect.